Visualization of Complex Laplace's Equations on a Hollow Rectangle. Issue 3 (3rd July 2018) - Hu, Hai-Ping
Abstract: In the investigation, the complex geometry domain is a hollow rectangle. The governing equations are expressed with complex Laplace's equations. And the analysis is solved by point-matching method. Besides, the results of numerical calculation are obtained by using Visual C ++ . In the present paper, visualization and image processing obtained from mathematical formulation of the complex Laplace's equations on a hollow rectangle. Then, the local values and the mean values of the function are also discussed in the article. We hope the results can further apply in the problem of fluid flow and heat conduction. Abstract :